-scanning under monochromatic laser pumping: a study of saturatable absorption in a suspension of multiwalled carbon nanotubes. (August 2016) - Mikheev, G.M.; Krivenkov, R.Yu.; Mikheev, K.G.; Okotrub, A.V.; Mogileva, T.N.
Abstract: A system has been developed and designed based on a single-mode single-frequency passive -switched pulsed laser to investigate with high accuracy the nonlinear optical properties of a liquid placed in an optical cell with uncoated input windows. The efficiency of this system is demonstrated by examples of studying the saturable absorption of an aqueous suspension of multiwalled carbon nanotubes and the nonlinear absorption of a colour glass filter ZhS18 at a wavelength of .